Tomographic Study of the Malformation Complex in Correlation With the Genotype in Patients With Robinow Syndrome: Review Article - Ali Al Kaissi MD, MSc; Vladimir Kenis MD, PhD; Mohammad Shboul PhD; Franz Grill MD; Rudolf Ganger MD, PhD; Susanne Gerit Kircher MD, MSc (SAGE Publishing, 2020)
We aimed to understand the etiology behind the abnormal craniofacial contour and other clinical presentations in a number of children with Robinow syndrome. Seven children with Robinow syndrome were enrolled in this study (autosomal recessive caused by homozygous mutations in the ROR2 gene on chromosome 9q22, and the autosomal dominant caused by heterozygous mutation in the WNT5A gene on chromosome 3p14). In the autosomal recessive (AR) group, the main clinical presentations were intellectual, disability, poor schooling achievement, episodes of headache/migraine, and poor fine motor coordinative skills, in addition to massive restrictions of the spine biomechanics causing effectively the development of kyposcoliosis and frequent bouts of respiratory infections. Three-dimensional reconstruction computed tomography scan revealed early closure of the metopic and the squamosal sutures of skull bones. Massive spinal malsegmentation and unsegmented spinal bar were noted in the AR group. In addition to severe mesomelia and camptodactyly, in the autosomal dominant (AD) group, no craniosynostosis but few Wormian bones and the spine showed limited malsegemetation, and no mesomelia or camptodactyly have been noted. We wish to stress that little information is available in the literature regarding the exact pathology of the cranial bones, axial, and appendicular malformations in correlation with the variable clinical presentations in patients with the 2 types of Robinow syndrome.